Kelayakan Usaha Tambak Udang Vaname (Litopenaeus vannamei) Di Desa Jogosimo Kecamatan Klirong Kabupaten Kebumen: The feasibility of vannamei shrimp farming (Litopenaeus vannamei) in Jogosimo Village, Klirong District, Kebumen Regency - Rosid, Riza Amin; Sri Lestari, Widya; Dwi Etika Rini, Wulandari (Journal of Agricultural Social and Business, 2025)
This study aimed to analyze the feasibility of vannamei shrimp farming in Jogosimo Village, Klirong District, Kebumen Regency. The research employed a quantitative approach using a case study method. Sampling was conducted through a census of 5 respondents, specifically vannamei shrimp pond owners in Jogosimo Village. The data used consisted of both primary and secondary data, collected through observation, interviews, and documentation techniques. Data analysis was performed using profitability analysis, Benefit-Cost Ratio (BCR), Revenue on Cost Ratio, and Break-Even Point (BEP). The results indicated that the average profit for vannamei shrimp pond owners in Jogosimo Village was IDR 25,093,393 per production cycle. The vannamei shrimp farming enterprise in Jogosimo Village, Klirong District, Kebumen Regency was deemed feasible, with an average BCR is 0.27 (> 0), the average RCR is 1.27 (> 1), the BEP price is IDR 25,728,817, and the BEP production is 602 kg. The average selling price of vaname shrimp is IDR 42,767.5 /Kg and the average quantity of vaname shrimp production is 2,366 kg.